Morphological study of anomalies of lobes and Segments of human liver - SHARMILA ARISTOTLE (International Journal of Pharma and Bio Sciences, 2016)
Objective: To identify various morphological variations in surface of human liver. Materials and Methods: The study was conducted in 60 adult human liver specimens by dissection method. Results: out of 60 specimens studied 25cases (41%) showed variations. Presence of additional lobe in 3 cases (5%); accessory fissures in 8 cases (13%); short gall bladder in 3 cases (5%); elongated left lobe in 2 cases (3.3%); very small left lobe in 1 case (1.6%);absence of quadrate lobe in 2 cases (3.3%);very small quadrate lobe in 1 case (1.6%);absence of fissure for ligamentum teres 1 case (1.6%); incomplete fissure for ligamentum teres in 3 cases (5%); prominent caudate process in 1 case (1.6%).Conclusion: Thorough knowledge of these variations is a must for surgeons for planning any surgeries and to radiologist for correct interpretation of diagnosis and treatment occurring in that region.